The Ozonolysis of α-Terpineol - Unusual Formation of a 6,6-Dimethylfulvene Epoxide - Alan F. Thomas; Celia Perret; Gérald Bernardinelli (CHIMIA)
Ozonolysis of α-terpineol (1) followed by steam distillation in the presence of acid is known to give 4-isopropylidenecyclopentenyl methyl ketone (3). In the absence of light, the latter is oxidized by air to the 4-(1-hydroperoxy-1-methylethyl)-1,3-cyclopentadien-1-yl derivative 4. On silica gel this compound formed two possible dimers (5, 6) of 3-acetyl-6,6-dimethylfulvene epoxide, the structures of which were established by X-ray crystallography. This work establishes by analogy, the stereochemistry of dimethylfulvene epoxide dimers previously described.